On the Nobel Prize in Physics, Controversies, and Influences (Global Journal of Science Frontier Research, 2013)
The Nobel Prizes were established by Alfred Bernhard Nobel for those who confer the "greatest benefit on mankind", and specifically in physics, chemistry, peace, physiology or medicine, and literature. In 1968 the Nobel Memorial Prize in Economic Sciences was established. However, the proceedings, nominations, awards, and exclusions have generated criticism and controversy. The controversies and influences related to the Nobel Physics Prize are discussed. The 1993 Nobel Prize in Physics was awarded to Hulse and Taylor, but the related theory was still incorrect as Gullstrand conjectured. The fact that Christodoulou received honors for related errors testified, "Unthinking respect for authority is the greatest enemy of truth" as Einstein asserted. The strategy based on the recognition time lag failed because of mathematical and logical errors. These errors were also the obstacles for later crucial progress. Also, it may be necessary to do follow up work after the awards years later since an awarded work may still be inadequately understood. Thus, it is suggested: 1) To implement the demands of Nobel's will, the Nobel Committee should rectify their past errors in sciences. 2
Keywords: controversies; nobel prize; errors; influences; suggestions